Effectiveness of intravenous ferric carboxy maltose(FCM ) in improving hemoglobin level amongst postpartum women with moderate to severe anemia in a tertiary care hospital - Sumitra Yadav; Surabhi Porwal; Namrata Pandey (International Journal of Health and Clinical Research, 2022)
Background: Postpartum Anemia (PPA)has been defined as hemoglobin(Hb)of <10 gm% during the postpartum period. The most common cause of anaemia in the world is iron deficiency. Each ml of blood loss results in loss of 0.5 mg iron. Because FCM has a neutral pH and physiological similarity, it can be given in high doses over a short period of time with minimal danger of hypersensitive reactions, and no test dosage is necessary. The safety and efficacy of IV FCM in the treatment of postpartum iron deficient anaemia are assessed in this study. Aims & objectives: Present study was done to estimate the changes in Hb level 6 weeks after IV FCM administration in postpartum women with Hb level of 5–9 g/dl who delivered at our tertiary care institute. Materials & methods: This was a prospective observational study conducted at MGMMC & MY Hospital Indore's Department of Obstetrics and Gynecology (MP).Study was conducted after taking ethical clearance. Total 100 patients were included in present study. Patients received single dose of 1 gm IV FCM. Hb, PCV, RBC indices, Serum ferritin and reticulocyte count were reassessed on day 42 of the treatment. The data was analysed statistically. A p value of< 0.05 was considered significant for all statistical purposes. Results: In this study most common age group was 21-25 years(47%),patients with parity 2 were most common (39%).(53%)study patients had vaginal delivery,(42%)had Caesarean delivery & (5%) had instrumental delivery. Statistically significant difference was noted between baseline & day 42 values of Hb, Serum ferritin, & RBC indices. Conclusion: Administration of single dose of IV FCM offers a promising treatment for pregnant women with moderate to severe iron defeciency anemia.